Garfield's Halloween adventure [videorecording (DVD)] - Davis, Jim, 1945 July 28- (Public Media Distribution, 2018)
It's time to trick-or-treat with Garfield! Garfield and Odie put on their pirate costumes to get as much Halloween candy as possible. After a successful night trick-or-treating, Garfield spots even more houses across the river! But once they get there, Garfield and Odie find themselves at a haunted house - where ghostly pirates are expected to arrive any minute.